1983
DOI: 10.1068/p120477
|View full text |Cite
|
Sign up to set email alerts
|

Visual, Kinaesthetic and Cross-Modal Development: Relationships to Motor Skill Development

Abstract: The ability of children between the ages of 5 and 10 years to match the length of lines within and between the modalities of vision and kinaesthesis was studied. No evidence was found for specific increases in cross-modal skill which could not be explained in terms of within-modal development. Performance in the perceptual task was related to measures of developing motor skill in the children. Substantial relationships were found between performance on the within-modal tasks and motor skill, but no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…In accordance with the account of Hulme and his coworkers (Hulme, Biggerstaff, et al, 1982 ;Hulme, Smart, et al, 1982 ;Hulme et al, 1983Hulme et al, , 1984Lord & Hulme, 1987a, 1988a, the meta-analysis indicated that numerous studies support the hypothesis that children with motor impairment have difficulties with processing visual information. The DCD groups had particular difficulty with visuospatial processing whether or not a motor response was involved ; for the main visual categories cited above, combined effect sizes were large.…”
Section: Information Processing Deficits In Children With Dcdsupporting
confidence: 74%
See 2 more Smart Citations
“…In accordance with the account of Hulme and his coworkers (Hulme, Biggerstaff, et al, 1982 ;Hulme, Smart, et al, 1982 ;Hulme et al, 1983Hulme et al, , 1984Lord & Hulme, 1987a, 1988a, the meta-analysis indicated that numerous studies support the hypothesis that children with motor impairment have difficulties with processing visual information. The DCD groups had particular difficulty with visuospatial processing whether or not a motor response was involved ; for the main visual categories cited above, combined effect sizes were large.…”
Section: Information Processing Deficits In Children With Dcdsupporting
confidence: 74%
“…With respect to perceptual processing, putative deficits include visual perception (Hulme, Biggerstaff, Moran, & McKinlay, 1982 ;Hulme, Smart, & Moran, 1982 ;Hulme, Smart, Moran, & Raine, 1983 ;Hulme, Smart, Moran, & McKinlay, 1984 ;Lord & Hulme, 1987a, 1988a, kinaesthetic perception (the perception of limb movement and limb position) (Bairstow & Laszlo, 1981 ;Laszlo & Bairstow, 1983, 1985Laszlo, Bairstow, Bartrip, & Rolfe, 1988), and cross-modal perception (or the transfer of information between sensory modalities) (Newnham & McKenzie, 1993). With respect to perceptual processing, putative deficits include visual perception (Hulme, Biggerstaff, Moran, & McKinlay, 1982 ;Hulme, Smart, & Moran, 1982 ;Hulme, Smart, Moran, & Raine, 1983 ;Hulme, Smart, Moran, & McKinlay, 1984 ;Lord & Hulme, 1987a, 1988a, kinaesthetic perception (the perception of limb movement and limb position) (Bairstow & Laszlo, 1981 ;Laszlo & Bairstow, 1983, 1985Laszlo, Bairstow, Bartrip, & Rolfe, 1988), and cross-modal perception (or the transfer of information between sensory modalities) (Newnham & McKenzie, 1993).…”
Section: Processing Deficits In Dcdmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the present study, the level of multisensory facilitation observed did not correlate with either age or motor reaction times. In a relatively early study, Hulme, Smart, Moran and Raine (1983) also found no relationship between visual‐kinaesthetic integration and motor skill development. In the current study, both children and adults were significantly faster in response to audio‐visual than purely visual stimuli.…”
Section: Discussionmentioning
confidence: 91%
“…1965; Illingworth 1968; Reuben & Bakwin 1968; Dare & Gordon 1970; Lesny 1980; Shaw et al . 1982; Hulme et al . 1983; Heilman & Rothi 1993).…”
Section: Introductionmentioning
confidence: 99%